Perlindungan Hukum Bagi Pemegang Saham Yang Kehilangan Kepemilikan Saham (International Forum of Researchers and Lecturers, 2023)
This legal research is Legal Protection for shareholders who experience loss of share ownership. The problem in this study is how the form of legal protection for shareholders in terms of related laws. This legal research is taken from a normative juridical approach which is a research by examining all laws and regulations related to the problem. The data used is secondary data consisting of primary and secondary legal materials. The end of this legal research is to answer the form of legal protection for shareholders who lose their share ownership. Keywords: Shares, Legal Protection, Loss of Share Certificate Ownership.